2012
DOI: 10.1073/pnas.1203472109
|View full text |Cite
|
Sign up to set email alerts
|

Structural engineering of a phage lysin that targets Gram-negative pathogens

Abstract: Bacterial pathogens are becoming increasingly resistant to antibiotics. As an alternative therapeutic strategy, phage therapy reagents containing purified viral lysins have been developed against Grampositive organisms but not against Gram-negative organisms due to the inability of these types of drugs to cross the bacterial outer membrane. We solved the crystal structures of a Yersinia pestis outer membrane transporter called FyuA and a bacterial toxin called pesticin that targets this transporter. FyuA is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 34 publications
0
109
0
2
Order By: Relevance
“…Furthermore, we demonstrate that genes encoding bacterial systems for iron acquisition, including the yersiniabactin system, are highly expressed during natural, uncomplicated cystitis in women. Overall, our data support the yersiniabactin system as a therapeutic target to prevent or treat UPEC-mediated UTI and reinforce the potential of the yersiniabactin system as a common target for several, increasingly multidrug-resistant, Gram-negative enteric pathogens (38,39).…”
Section: Figmentioning
confidence: 75%
“…Furthermore, we demonstrate that genes encoding bacterial systems for iron acquisition, including the yersiniabactin system, are highly expressed during natural, uncomplicated cystitis in women. Overall, our data support the yersiniabactin system as a therapeutic target to prevent or treat UPEC-mediated UTI and reinforce the potential of the yersiniabactin system as a common target for several, increasingly multidrug-resistant, Gram-negative enteric pathogens (38,39).…”
Section: Figmentioning
confidence: 75%
“…The two other HPI operons encode Ybt biosynthesis-associated proteins and the transcription factor, YbtA, which is necessary for expression of all four HPI operons (19). FyuA is a β-barrel outer membrane protein which imports Ybt complexes into the periplasm using energy from the proton gradient across the inner membrane by coupling to the inner membrane TonB/ExbB/ExbD complex (20). YbtP and YbtQ are putative ABC transporters that are thought to form a heterodimer (termed YbtPQ) in the inner membrane and are necessary for cellular utilization of Ybt-bound iron (8,18,21).…”
mentioning
confidence: 99%
“…This hybrid toxin killed Yersinia and Escherichia coli strains and also bypassed the pesticin immunity (PIM) [111]. Furthermore, Ply187-derived CD, when fused to non-SH3b CBD from phage phi13 endolysin NM3, protects mice against MRSA [112].…”
Section: Endolysins-phage Enzymes Degrading Peptidoglycanmentioning
confidence: 99%
“…In 2012, Lukacik et al showed that the fusion of FyuA-binding domain of pesticin and T4 lysozyme utilizes FyuA for transport across the OM of Gram-negative Yersinia pestis [111]. This hybrid toxin killed Yersinia and Escherichia coli strains and also bypassed the pesticin immunity (PIM) [111].…”
Section: Endolysins-phage Enzymes Degrading Peptidoglycanmentioning
confidence: 99%